Communicating social and environmental issues effectively - Reed, Betsy (Emerald Publishing Limited, 2020)
This is the definitive guide to planning and delivering great communications on complex social and environmental issues. Including real-world case studies, practical exercises and clear frameworks, this book helps leaders, managers and marketing professionals plan, risk-proof and execute effective communications strategies.
Keywords: Communication in the environmental sciences.; Communication in the social sciences.; Environmental policy -- Social aspects.; Communication en environnement.; Environnement -- Politique gouvernementale -- Aspect social.; Business communication & presentation.; Business & Economics -- Business Communication -- General.; Communication in the environmental sciences; Communication in the social sciences; Environmental policy -- Social aspects